PERBAIKAN BEBAN KERJA KERJANTARA DALAM KEGIATAN PENEBANGAN SECARA MEKANIS MELALUI PENERAPAN PRINSIP ERGONOMI - Soenarno Soenarno; Maman Mansyur Idris (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
Tree felling operations in Indonesia are commonly done by standing or bending workers, using chain saws. These techniques cause high stump residues (about 8.94%) and increase workers' energy consumption by 12% for standing and 55% for bending workers' positions.From ergonomics point of view, above techniques cause body position to be less natural, produce longer static muscular work, reduce work hours, create early fatique and physiological effect like work stress.This paper described the effect of improved felling method on work stress of chain saw operators and construction wood production. An investigation was carried out in two private forest companies in Central Kalimantan in 1988. The results are as the following:The improved felling method decreases work stress of chain saw operators; showed by the reduction of pulse rate to the amount of 13-15 beats/minute. The improved method of felling trees with buttress heights of < 50 cm and 50-150 cm cause the increase in construction wood products about 0.354 m3 and 0.542 m3 per tree felled, respectively.